Extensive graded reading with engineering students: Effects and outcomes - Hagley, Eric (Reading in a foreign language, 2017)
Extensive graded reading (EGR) was carried out with a cohort of 600 engineering students in a university in northern Japan. Pre-and post-surveys were conducted to discover changes in the general reading habits of students, their attitudes toward the assessment method and how goals changed over the course of study. The first survey was carried out in week 2 of the 15-week course and the second in week 13. An analysis of changes showed that EGR was generally well accepted, that students' perceptions of studying English seemed to improve, that students spent a little less time on recreational reading to compensate for the increases required in the EGR course and that most read considerably more running words than their initial goals. In addition, the results suggest that the short MoodleReader quiz format used for assessment was also generally well received by students. Implications for teachers using EGR are discussed.